Structural and physicochemical properties of bracken fern (Pteridium aquilinum) starch - Li, Kehu; Zhang, Tongze; Ren, Huanhuan; Zhao, Wei; Hong, Siqi; Ge, Yongyi; Li, Xiaoqiong; Corke, Harold (Frontiers in Nutrition, 2023)
Introduction Bracken fern (Pteridium aquilinum) starch is a non-mainstream, litter-researched starch, thus the starch characteristics remain largely unknown. Methods The structural and physicochemical properties of two bracken starches were systematically investigated, by use of various techniques that routinely applied in starch analysis. Results and Discussion The starches had amylose contents of 22.6 and 24.7%, respectively. The starch granules possessed C-type polymorph with D (4,3) ranging from 18.6 to 24.5 μm. During gelatinization event, the bracken starches showed lower viscosity than typical for rice starch, and lower gelatinization temperature than typical for cereal starches. After gelatinization event, bracken starches formed much softer and sticky gel than rice and potato starch. The molecular weight and branching degree (indexed by Mw, Mn and Rz values) of bracken starches were much higher than starches of many other sources. The branch chain length distributions showed that the bracken starches were structurally similar to some rice varieties (e. g. BP033, Beihan 1#), as reflected by proportions of A, B1, B2, and B3 chains. Notable differences in some starch traits between the two bracken starches were recorded, e. g. amylose content, gel hardness, gelatinization temperature and traits of structural properties. This study provides useful information on the utilization of bracken starch in both food and non-food industries.